The determination of quercetin in Plectranthus scutellarioides(L.) R.Br. leaves extract and its In SilicoStudy on Histamine H4 Receptor - Moektiwardoyo, Moelyono; Levita, Jutti; Sidiq, Syafrudin Purnama; Ahmad, Khoziah; Mustarichie, Resmi; Subarnas, Anas; ., Supriyatna (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Plectranthus scutellarioides (L.) R.Br., or jawer kotok, Family Lamiaceae, grows widely in Indonesia, and has a long history of therapeutic usage in Indonesian traditional jamuto cure various diseases. The brownish purple leaves of Plecranthus contain alkaloids, saponin, flavonoids, tannin, volatile oils, and quercetin which has been proven to exert antiinflammatory activity. In this research, a determination of quercetin in Plecranthus leaves extract was performed and followed by a study of its interaction with histamine H4 receptor to understand its anti-inflammatory activity. The dry leaves were macerated by using a mixture of methanol and water (1:1) for 48 hours and the solvent was evaporated at low temperature (40-50oC). Analysis of quercetin in the extract was performed by using reversed-phase HPLC method LC-10AT VP (Shimadzu), Atlantis Hilicsilica C18 (Waters®) 150 mm x 4.6 mm, 5 µm as stationary phase and a mixture of acetonitrile, phosphoric acid, and methanol (40:50:10), flow rate 0.8 mL/minute. In silicostudy of quercetin with histamine H4 receptor was performed by using AutoDock Tools 3.0.5. Histamine H4 receptor (H4R) belongs to G protein-coupled receptors which is involved in arthritis, asthma, and inflammations. The 3D structure model of H4R was built by using MODELLER 9v7. Quercetin contained in Plecranthus leaves extract was 0.05 %. This compound interacted with H4R viahydrogen bond formation with Lys158 (2.006 Å) and Glu182 (2.048 Å), and van der Waals interaction with Trp90, Leu91, Asp94, Tyr95, Phe168, Thr178, Ser179, Tyr319, Phe344, and Tyr340, therefore Plecranthus leaves extract might have a chance to be used as histamine H4 receptor inhibitor.Key words : histamine H4 receptor, in silico study, Plecranthus leaves, Plectranthus scutellarioides, quercetin